Mitra Clip: Looking at its chance in developing country - Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2014)
Looking at developed countries data on valvular heart diseases, mitral regurgitationis one of the most commonly encountered valvular lesions. Moderate to severe regurgitation present in up to 30% of patients with various clinical subsets. Mitral regurgitation severity has been positively correlated with the subsequent development of heart failure and death.1-4The 2008 ACC/AHA guidelines describe three types of MV operations: (i) MV repair; (ii) MV replacement with chordal preservation; and (iii) MV replacement with removal of the mitral apparatus. The ACC/AHA guidelines support MV surgery for patients with severe (3– 4+) MR who are symptomatic with preserved LV size and function, asymptomatic with LV dysfunction or increased LV size, who have recent onset atrial fibrillation or evidence of pulmonary hypertension, or in symptomatic patients with severe LV dysfunction (LVEF ?30%) despite optimal medical therapy.Currently, a new percutaneous approach for treating mitral regurgitation (so called MitraClip) which involves mechanical edge-to-edge coaptation of the mitral leaflets has been developed. The device mechanism is analogous to the surgical Alfieri technique.MitraClip (Abbott Vascular, Abbott Park, Illinois, USA; formerly manufactured by EvalveInc, Menlo Park, California, USA) has been approved by FDA last year.5Since 2008 almost 4000MitraClip have been implanted all over the world (Figure 1).6Overall, the procedure has proven to be safe with exceedingly low rates of fatal or life-threatening complications. Additionally, significant improvements in functional capacity and quality of life have been reported following MitraClip implantation. However, apart from these encouraging results, open questions remain to be addressed, particularly about long term durability and clinical efficacy, and the selection of the most appropriate candidates for MitraClip implantation. As the experience with this procedure continues to expand, larger studies are expected that will help to further define the role of the MitraClip procedure among established therapies.6Patient selection is utmost important to gain procedural success. Two main criteria of Endovascular Valve Edge-to-Edge Repair Study (EVEREST) for patient selection are clinical and anatomical criteria. Clinical criteria comprise of moderate-to-severe (3+) and severe (4+) mitral regurgitation, meeting class I indications for intervention (MVR or mitral valve replacement) by the ACC/AHA or ESC guidelines, mitral reguritationaetiology limited to degenerative or functional, non-rheumatic or -endocarditic origin, andhigh surgical risk by EuroSCORE or STS scores. Anatomical criteria comprise of mitral regurgitation originating from the central 2?3 of the valve, mitral orifice area ?4 cm2, meeting criteria for degenerative mitral regurgitation (i.e. flail gap <10 mm, flail width <15 mm), meeting criteria for functional mitral regurgitation (i.e. coaptation depth ? 11 mm, coaptation length ? 2 mm).7, 8